Barriers in prescribing antidiabetic medications with cardiovascular benefits: practice, experience, and attitudes of GPs in Croatia - Tomislav Kurevija; Dunja Šojat; Ines Bilić-Ćurčić; Silvija Canecki-Varžić; Ljiljana Trtica-Majnarić (BMC Primary Care)
Abstract Background The treatment approaches of type 2 diabetes (T2D) are being transformed, due to the availability of novel antidiabetic medications, sodium-glucose co-transporter 2 inhibitors (SGLT2ins), and glucagon-like peptide-1 receptor agonists (GLP-1 RAs). Despite their proven beneficial effects, recent research points to their insufficient prescription. This study aimed to reveal the prescription rates of SGLT2ins and GLP-1 RAs among general practitioners (GPs) in Croatia and to examine factors associated with their low self-confidence in prescribing them. Methods A self-designed survey questionnaire was used and delivered to the GPs’ e-mail addresses in digital format. The data on the number of individuals diagnosed with T2D and prescribed new antidiabetic medications were checked by the respondents in their electronic database. Factors associated with lower GPs` self-confidence in prescribing SGLT2ins and GLP-1 RAs were assessed by bivariate and multivariate logistic regression analyses. Results The study included 168 GPs (66.1% women; 49.4% specialists in family medicine) and a cohort of 23,036 individuals with T2D. The prescription rates of SGLT2ins and GLP-1 RAs were 21.0% and 14.4%, respectively. Specialists stated a higher level of self-confidence in prescribing these medications, compared to other respondents. In the multivariate models, a factor that was shown to reduce the likelihood of low GPs` self-confidence in prescribing SGLT2ins was “familiarity with the side effects of these medications” (OR = 0.03), while factors that increased this likelihood were: “being familiar with GLP-1 RAs` side effects” (OR = 4.8), “an insufficient knowledge and experience of GPs in adjusting two target outcome measures to the same patient” (OR = 2.2), and “the GPs` assumption that the new guidelines` protocol which separates two target outcome measures is useful only in some cases but not in all” (OR = 5.4). Regarding GLP-1 RAs, only one factor – “familiarity of GPs with GLP-1 RAs side effects”, was shown to reduce the probability of GPs` low self-confidence in prescribing this group of medications (OR = 0.27). Conclusion It is of the utmost importance to identify barriers the GPs face when prescribing these medications, as well as to suggest potential strategies to optimize their prescription.